Cognitive Self-Regulation Correlated with Goals Achievement of the Students of University of Baghdad - Jwad, Jafar.J. (International Journal of Psychosocial Rehabilitation, 2020)
Self-regulation is considered one of the significant factors which enable the student to overcome the educational hurdles through enhancing motivation and learning control for achievement, as it helps the student to sustain the factors that contribute to ongoing concentration on work details which in turn conduce the achievement of highly valued goals albeit their attraction. This enables the student to delay the immediate rewards and to head towards long-range goals which carry out the student psyche and position. The current research aims at approaching the self-regulation of the students of the University of Baghdad and the correlation between self-regulation and goals achievement. The research is confined to 300 male and female students of the University of Baghdad. It has adopted the cognitive regulation measurement by Pintrich, (2000) and the goals achievement measurement by Al-Zuhairi, (2013). The results have revealed that students practice the cognitive self-regulation and the goals achievement. There is a positive correlation between the cognitive self-regulation and goals achievement. As for the gender variable, the difference has no statistical significance.